Respuesta :

Given Equations :

✿  5x + 3y = -6 -------------- [1]

✿  3x - 2y = 4 -------------- [2]

Multiplying Equation [1] with 2, We get :

⇒ 10x + 6y = -12 ----------- [3]

Multiplying Equation [2] with 3, We get :

⇒ 9x - 6y = 12 ---------- [4]

Adding Both Equations [3] and [4], We get :

⇒ (10x + 6y) + (9x - 6y) = -12 + 12

⇒ 19x = 0

⇒ x = 0

Substituting x = 0 in Equation [1], We get :

⇒ 5(0) + 3y = -6

⇒ 3y = -6

⇒ y = -2

⇒ (x , y) = (0 , -2)

Option (a) is the Answer

Answer: A (0, -2)

Step-by-step explanation:

5x + 3y = -6   →   2(5x + 3y = -6)   →   10x + 6y = -12

3x  - 2y =  4   →   3(3x  - 2y =  4)   →   9x  - 6y = 12

                                                          19x           =  0

                                                              x          =  0

Now, input "x = 0" into one of the equations and solve for y:

5x + 3y = -6

5(0) + 3y = -6

         3y = -6

           y = -2


ACCESS MORE